Financial modeling - Benninga, Simon; Mofkadi, Tal (Cambridge, Massachusetts : The MIT Press, 2021)
"A revision of a leading finance textbook for the advanced undergraduate/Master's market"--
Revised edition of Financial modeling, [2014]
Includes bibliographical references and index.
AAL
Keywords: Finance -- Mathematical models